Comparison of Percutaneous Kyphoplasty With or Without Posterior Pedicle Screw Fixation on Spinal Sagittal Balance in Elderly Patients With Severe Osteoporotic Vertebral Compression Fracture: A Retrospective Study - Zhou, Quan; Zhang, Junxin; Liu, Hao; He, Wei; Deng, Lei; Zhou, Xinfeng; Yang, Huilin; Liu, Tao (Frontiers in Surgery, 2022)
Objective: To compare the effects of percutaneous kyphoplasty (PKP) with or without posterior pedicle screw fixation (PPSF) on spinal sagittal balance in elderly patients with severe osteoporotic vertebral compression fracture (sOVCF). Methods: From January 2016 to December 2018, 102 elderly patients with single-level thoracolumbar sOVCF were enrolled. Among them, 78 cases underwent PKP (Group A), and 24 cases underwent PPSF+KP (Group B). Clinical evaluation included perioperative parameters, Oswestry Disability Index (ODI) and Visual Analog Scale (VAS) for back pain; Radiographic evaluation included anterior vertebral height (AVH) and rate (AVHr), local kyphotic angle (LKA), and spino-pelvic sagittal balance parameters. Results: Perioperative parameters including operation time, blood loss, fluoroscopic time and hospital stay in Group A were less than those in Group B (p<0.05). Compared with the preoperative results, the ODI and VAS scores of both groups decreased significantly in the three follow-ups after surgery (p<0.05). The postoperative ODI and VAS scores of Group A were significantly better than those of Group B, but the results were opposite at the final follow-up (p<0.05). Compared with the preoperative values, except that there was no significant difference in pelvic incidence (PI) (p>0.05), other radiographic parameters of both groups were improved significantly in the three follow-ups after surgery (p<0.05). The AVH, AVHr, LKA and lumbar lordosis (LL) in Group B were better than those in Group A in the three follow-ups after surgery (p<0.05). At the final follow-up, the sacral slope (SS) and pelvic tilt (PT) differed significantly between the two groups (p<0.05). Conclusions: Both PPSF+KP and PKP can achieve favorable clinical outcomes and maintain the spinal sagittal balance well. Compared with PPSF+KP, PKP showed more significant advantages in the early postoperative period. However, in the long-term follow-up, PPSF+KP showed better clinical outcomes and may be better than PKP in maintaining spinal sagittal balance.